PEMANFAATAN MEDIA SOSIAL SEBAGAI ALTERNATIF DALAM MEMPERKENALKAN PRODUK PELAKU USAHA - Muhammad Sholeh; Suraya Suraya; Anis Zaitunah (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Nowadays, social media has become one of the people's lifestyle, especially among young people. The existence of social media must be used by SMEs (small and medium enterprises) in marketing products. One of the social media that can be used is Instagram. Efforts to disseminate social media were made to representatives of UKM in Kasihan District. In this socialization, the focus of social media is Instagram. Based on the results of the questionnaire given to the socialization participants, 100% have used social media in marketing products and all respondents answered using WhatsApp as social media while 30% used Instagram. The method of socialization is carried out by providing training and accompanying and providing an overview of the use of Instagram as a promotional media. Providing an overview of the use of Instagram was conveyed by speakers from business actors who have used Instagram as a promotional medium.